Influence of CO2 Degassing on the Microbial Community in a Dry Mofette Field in Hartoušov, Czech Republic (Western Eger Rift) - Liu, Qi; Kämpf, Horst; Bussert, Robert; Krauze, Patryk; Horn, Fabian; Nickschick, Tobias; Plessen, Birgit; Wagner, Dirk; Alawi, Mashal (Frontiers in Microbiology, 2018)
The Cheb Basin (CZ) is a shallow Neogene intracontinental basin filled with fluvial and lacustrine sediments that is located in the western part of the Eger Rift. The basin is situated in a seismically active area and is characterized by diffuse degassing of mantle-derived CO2 in mofette fields. The Hartoušov mofette field shows a daily CO2 flux of 23–97 tons of CO2 released over an area of 0.35 km2 and a soil gas concentration of up to 100% CO2. The present study aims to characterize the geo-bio interactions provoked by the influence of elevated CO2 concentrations on the geochemistry and microbial community of soils and sediments. To sample the strata, two 3-m cores were recovered. One core stems from the center of the degassing structure, whereas the other core was taken 8 m from the ENE and served as an undisturbed reference site. The sites were compared regarding their geochemical features, microbial abundances, and microbial community structures. The mofette site is characterized by a low pH and high TOC/sulfate contents. Striking differences in the microbial community highlight the substantial impact of elevated CO2 concentrations and their associated side effects on microbial processes. The abundance of microbes did not show a typical decrease with depth, indicating that the uprising CO2-rich fluid provides sufficient substrate for chemolithoautotrophic anaerobic microorganisms. Illumina MiSeq sequencing of the 16S rRNA genes and multivariate statistics reveals that the pH strongly influences species distribution and explains around 38.7% of the vertical species distribution at the mofette site and 35.3% of the variance between the mofette site and the undisturbed reference site. Accordingly, acidophilic microorganisms (e.g., Acidobacteriaceae and Acidithiobacillus) displayed a much higher relative abundance at the mofette site than at the reference site. The population analyses revealed the different species involved in soil organic matter degradation under aerobic and anaerobic conditions. Furthermore, the microbial community at the mofette site is characterized by a high relative abundance of taxa involved in sulfur and iron cycling. The present study provides intriguing insights into microbial life and geo-bio interactions in an active seismic region dominated by emanating mantle-derived CO2-rich fluids.